2003
DOI: 10.1021/ac035122z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter and Shigella Species in Food Samples Using an Array Biosensor

Abstract: Campylobacter and Shigella bacteria are common causes of food- and water-borne illness worldwide. There is a current need in food, medical, environmental, and military markets for a rapid and user-friendly method of detecting such pathogens. The array biosensor developed at the NRL encompasses these qualities. In this study, 25-min, sandwich immunoassays were developed for the detection of Campylobacter and Shigella species in both buffer and a variety of food and beverage samples. The limit of detection for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 27 publications
(56 reference statements)
1
51
0
Order By: Relevance
“…14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Table 1 provides detailed information on the assays including limits of detection (LOD). The LOD was calculated as the lowest concentration tested which gave a signal 3 standard deviations above the blank.…”
Section: Antibody-based Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Table 1 provides detailed information on the assays including limits of detection (LOD). The LOD was calculated as the lowest concentration tested which gave a signal 3 standard deviations above the blank.…”
Section: Antibody-based Detectionmentioning
confidence: 99%
“…33 Due to public health risks, much of the recent work in assay development has concentrated on the rapid detection of foodborne contaminants. The NRL Array Biosensor has been used for the measurement of a number of protein toxins, such as staphylococcal enterotoxin B (SEB) 22,23 and botulinum toxoid A, 22 and bacteria, including Campylobacter spp., 29 Shigella spp., 29 Escherichia coli 32 and Salmonella enterica serovar Typhimurium, 28 in a variety of spiked food matrices. Analyte detection is rapid, with immunoassays taking 10 -45 min, is simple to perform and requires minimal sample processing.…”
Section: Antibody-based Detectionmentioning
confidence: 99%
“…Several PCR protocols using different molecular markers have been used for the detection of Shigella species in environmental, faecal, and food samples [15][16][17][18][19][20][21][22]. The invasion plasmid antigen H (IpaH) and the IpaABCD genes are virulence gene markers whose protein products are necessary for invasion of colonic epithelial cells.…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 99%
“…The array biosensor developed at the NRL encompasses these qualities. Ligler et al [30 ] reported on a sandwich immunoassaybased biosensor array that was developed for the detection of Campylobacter and Shigella species in both buffer and a variety of food and beverage samples. The limit of detection for Shigella dysenteriae in buffer and chicken carcass wash was 4.9×10 4 CFU/mL, whereas Campylobacter jejuni could be measured at concentrations as low as 9.7×10 2 CFU/mL.…”
Section: Antibody Based Biosensor Arraymentioning
confidence: 99%